Increasing cybersecurity awareness among teenagers through digital education and simulation - Riandari, Fristi; Tasril, Virdyra; Ritonga, Rama Prameswara (Lebah, 2024)
This community service aims to explore the role of digital education and simulation tools in enhancing cybersecurity awareness among teenagers. The review examines various educational methods, including e-learning platforms, gamification, and phishing simulations, to evaluate their effectiveness in increasing cybersecurity knowledge and skills. The methodology involves analyzing relevant studies from academic databases, combining both qualitative and quantitative research. Key findings suggest that interactive digital education and simulations significantly improve teenagers' ability to recognize and address online threats. However, challenges remain regarding long-term retention and engagement. The review highlights the growing importance of these tools in educating teenagers, emphasizing the need for their integration into educational settings. Trends include the use of gamification and simulations, while gaps in research, such as long-term effectiveness and cultural influences, remain. Recommendations for future initiatives include AI-driven simulations and incorporating cybersecurity education into social media platforms for broader reach.